2017
DOI: 10.1371/journal.pone.0169679
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Influenza Vaccination among Adults with Chronic Medical Conditions Vary by Age in the United States

Abstract: BackgroundPeople living with chronic health conditions exhibit higher risk for developing severe complications from influenza according to the Centers for Diseases Control and Prevention. Although racial and ethnic disparities in influenza vaccination have been documented, it has not been comprehensively determined whether similar disparities are present among the adult population with at least one such condition.ObjectiveTo study if racial and ethnic disparities in relation to influenza vaccination are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Overall, surveys of U.S. adults, while primarily focused on 2009 H1N1 vaccination, have also found healthcare provider recommendations, susceptibility and severity perceptions, and past experience with influenza illness and vaccination correlated with seasonal influenza vaccination [ 13 , 14 , 15 , 16 , 17 ]. Racial and ethnic differences also have been frequently documented [ 18 , 19 , 20 ], with the 2015–2016 seasonal vaccination rates ranging from 44.5% for non-Hispanic Whites to 36.6% for non-Hispanic Blacks to 34.4% for Hispanics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, surveys of U.S. adults, while primarily focused on 2009 H1N1 vaccination, have also found healthcare provider recommendations, susceptibility and severity perceptions, and past experience with influenza illness and vaccination correlated with seasonal influenza vaccination [ 13 , 14 , 15 , 16 , 17 ]. Racial and ethnic differences also have been frequently documented [ 18 , 19 , 20 ], with the 2015–2016 seasonal vaccination rates ranging from 44.5% for non-Hispanic Whites to 36.6% for non-Hispanic Blacks to 34.4% for Hispanics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One striking finding of our study is the lack of association between self-report of current flu vaccination and being diagnosed with a major chronic condition such as CVD, COPD, diabetes, stroke, and cancer. It has been previously shown that older African-Americans with chronic conditions have lower rates of flu vaccination [ 7 , 31 ]. A systematic review and meta-analysis of six decades of randomized clinical trials that compared flu vaccine versus placebo among individuals at high risk for CVD showed that the flu vaccine lowered the risk of major adverse cardiovascular events [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural attitudes towards seeking health care, lower literacy levels, higher unemployment rates, inadequate social support, and higher levels of chronic stress in rural areas may also increase risk of CVD [65,84] and attenuate the effects of efforts to improve cardiovascular health [85,86]. Variations in exposures such as extreme cold or hot temperature, air pollution, and influenza vaccination, may also have contributed to the disparities in MI hospitalization risks [87,88,89].…”
Section: Discussionmentioning
confidence: 99%